Mapping the grassland quality of the flooded plain based on Jilin-01 images with a red-edge spectral band - Chen, Ziqi; Zhang, Yanhong; Zang, Peng; Liu, Zhaoli; Zhao, Wenbin (Frontiers in Earth Science, 2023)
Aiming at the difficulty of quality evaluation of the flooded plain, high-resolution satellites remote sensing data with red-edge spectrum acquired from Jilin-01, and the Grassland Quality Index (GQI) is formed by Normalized Difference Vegetation Index (NDVI) and Normalized Difference Red Edge Index (NDRE) related to grassland quality and the first principal component of red-edge Chlorophyll Index obtained by principal component analysis. The GQI is applied to evaluate grassland quality in the flooded plain, an important grassland ecological barrier area in the west of Jilin Province, and verified using field measurement data. Results show that: (1) 80% of grasslands in Xianghai Nature Reserve are of medium quality, the grassland with good growth status accounts for about 15%, mainly concentrated in the wetland and swamp areas in the central south part of the reserve. (2) The correlation of the evaluation results is verified by using the survey field biomass, and the coefficient of the empirical correlation model established is 0.96, indicating a good consistency. This study is of practical significance for timely and accurate monitoring of grassland growth, which is beneficial to the development of livestock husbandry and the protection of ecological environment in northern China.